Prevalence and associated factors of prelacteal feeding among neonates admitted to neonatal intensive care units, North central Ethiopia, 2019 - Wubet Alebachew Bayih; Demewoz Kefale Mekonen; Solomon Demis Kebede (BMC, 2020)
Abstract Background Prelacteal feeding compromises the benefits of exclusive breastfeeding, thereby increasing neonatal malnutrition, infection and mortality. About 26% of the Ethiopian neonates are given prelacteal feeds and nearly 48% of whom are attributed to Amhara region. Besides, prior Ethiopian studies have shown significance of the problem at different community settings in the country. However, the prevalence and associated factors of prelacteal feeding among neonatal admissions has been overlooked in the country in general and in the study area in particular. Therefore, this study was aimed to assess the prevalence and associated factors of prelacteal feeding among neonatal admissions in the study setting. Methods A cross-sectional study was conducted among 321 mother-neonate pairs admitted to Neonatal Intensive Care Unit (NICU) of Debre Tabor General Hospital between September 2018 and February 2019. Every fourth mother neonate pair was included to the study. Multivariable logistic regressions were fitted to find out adjusted odds ratios (AORs) of factors associated with pre-lacteal feeding. Results The prevalence of prelacteal feeding was 20.2% [95% CI: 15.31-26.75%]. Plain water was the most common prelacteal food (32.3%). Factors associated with prelacteal feeding include rural residence (AOR = 4.07, 95% CI: 1.30, 12.81), primiparity (AOR = 4.50, 95% CI: 1.30-12.81), less than four ANC visits (AOR = 4.71, 95% CI: 1.23-17.84), spousal accompany to ANC (AOR = 0.20, 95% CI: 0.05-0.75), home delivery (AOR = 5.94, 95% CI: 1.80-19.67), having twin newborns (AOR = 6.69, 95% CI: 1.25, 35.91) and maternal belief on the purported advantages of prelacteal feeding (AOR = 2.74, 95% CI: 2.09-25.39). Conclusion and recommendation One out of five sick neonates was given prelacteal feeds. Twin neonates, home delivered neonates, rural neonates, neonates born to primiparous mothers, neonates delivered from mothers who had less than four ANC visits, neonates born to mothers who weren't accompanied by their spouse during ANC and those born to mothers who believe on the purported advantages of prelacteal feeding had higher odds of receiving prelacteal feeds. Therefore, mothers of these vulnerable neonates should be provided with more emphasis about counseling of infant and young child feeding practice during their stay at NICU.